Educational opportunities: dialogue between a brazilian teacher and a rwandan teacher - Castro, Carlos Henrique Silva de; Nyiramavugo, Marie Grace (Texto Livre, 2013)
Our purpose in these interviews is giving each other, and our audience, a personal frame, with basic information, of the education and the educational opportunities in our countries. We are two teachers studying in the USA. The first of these authors, Carlos Castro, is from Brazil. The second one, Marie Grace Nyiramavugo, is from Rwanda. We have experience in teaching for secondary school/high schools and universities/higher institutions.